Protective Activity and Underlying Mechanism of Ginseng Seeds against UVB-Induced Damage in Human Fibroblasts - Huijin Heo; Hana Lee; Jinwoo Yang; Jeehye Sung; Younghwa Kim; Heon Sang Jeong; Junsoo Lee (MDPI AG, 2021)
Ginseng seeds are rich in phytosterols, ginsenosides, and fatty acids, and can therefore be used in skincare to delay the aging process. Ginseng seed embryo (GSE) and ginseng seed coat (GSC) were separated from ginseng seeds (Panax ginseng Meyer). This study evaluated the protective activity and underlying mechanism of GSE and GSC on UVB irradiation-induced skin photoaging using Hs68 cells. Their bioactive compounds, including phytosterols, ginsenosides, tocopherols, tocotrienols, and fatty acids were determined by HPLC and GC. The levels of reactive oxygen species, matrix metalloproteinases (MMPs), and collagen levels were measured in human dermal fibroblast cell line, Hs68 cells. The antioxidant capacity and contents of total polyphenols and flavonoids were higher in GSC than those in GSE. Linoleic acid was the major fatty acid in both GSE and GSC. GSE and GSC treatment alleviated UVB-induced increase of reactive oxygen species (ROS), matrix metalloproteinase (MMP)-1, and MMP-3, resulting in reduced collagen degradation. Increased UVB-mediated phosphorylation of mitogen activated protein kinase (MAPK) and activator protein-1 (AP-1) was inhibited by GSE and GSC treatment. Moreover, GSE and GSC effectively upregulated transforming growth factor-β (TGF-β) 1 levels. It was found that ginseng seeds regulate the expression of TGF-β/Smad and MAPK/AP-1 pathways. Ginseng seeds contain various bioactive compounds and have protective activity against UVB-induced skin photoaging. Therefore, ginseng seeds have the potential for use in cosmeceutical preparations.